Recognition of Predator Type and Risk Level in Azure‐Winged Magpies (Cyanopica cyanus) Through Visual and Auditory Cues - Taijun Zuo; Jiaojiao Wang; Jiangnan Liu; Jianping Liu; Qindong Zhou; Jianhua Hou (Ecology and Evolution, 2024)
ABSTRACT Predation events are an important key factor determining the survival and reproduction of prey species. To cope, prey species have evolved various anti‐predator strategies, including mechanisms for accurate predator identification and distinguishing predator types and risk levels. Birds rely on visual, auditory, and olfactory cues to perceive and categorize predators. However, previous studies have focused on single sensory modalities and have largely been conducted during breeding seasons. Thus, analyses of the accuracy and differences in predator recognition cues, especially during non‐breeding periods, are needed. In this study, predator recognition in Azure‐winged Magpies (Cyanopica cyanus) was evaluated during the non‐breeding season. We examined responses to two predators, Common Kestrel (Falco tinnunculus) and Domestic Cat (Felis catus), and two non‐predators, Oriental Magpie (Pica serica) and Oriental Turtle Dove (Streptopelia orientalis). Using specimens and playback experiment, the ability of Azure‐winged magpies to identify threats through both visual and auditory cues was evaluated. The results showed that Azure‐winged Magpies can identify predator types through both visual and auditory cues, accurately distinguish threat levels, and adjust their foraging behavior accordingly. Notably, they exhibited the strongest anti‐predator response to Domestic Cats (frequently encountered under natural conditions), as evidenced by longer observation times, shorter foraging duration, and quicker flight responses. The results indicate that Azure‐winged Magpies can correctly identify predator types and threat levels through both visual and auditory cues and exhibit stronger anti‐predator behaviors with increasing apparent threat levels.